CHARACTERIZATION OF EQUILIBRIUM CONDITIONS OF ADSORBED SILICAGEL/WATER BED ACCORDING TO DUBININASTAKHOV AND FREUNDLICH - Afonso, M. R. A.; Silveira Jr., V. (Revista de Engenharia Térmica, 2005)
Systems of adsorption have been studied as an alternative for the cooling systems for saving electrical energy. The main advantage is the heat as the driving sources, for example, hot water or waste heat, widely used in the industries, and solar energy. The pair adsorbent/ adsorbate determines the behavior of these systems. Therefore, the knowledge of the equilibrium conditions between the adsorbent and the adsorbate is very important. The pair silica gel/water has the advantage of exploiting low-temperature heat sources. In this paper, the equilibrium conditions of the pair silica gel/water were investigated and the data were used to identify the coefficients of Dubinin-Astakhov equation and Freundlich equation. The experiments consisted of measuring temperature and pressure for different adsorbed mass of water in the adsorbent (silica gel). The amount of adsorbed mass (kg) per adsorbent mass (kg) used were: 0.007, 0.013, 0.024, 0.047, 0.092, 0.162 and 0.209. Both equations showed good agreement with experimental data, the coefficients of regression (R2) were 0.991 on the Dubinin-Astakhov equation and 0.993 for the Freundlich equation.